Downregulation of ATRX disrupts cell proliferation and cell cycle progression - Delorme, Marilyne (University of Ottawa (Canada), 2008)
ATRX is a chromatin remodelling protein of the SNF2 family of chromatin remodelling proteins. Mutations in the ATRX gene have been shown to cause the ATR-X syndrome, an X-linked mental retardation disorder. ATRX is part of a chromatin-remodelling complex with Daxx that localizes to PML nuclear bodies or pericentromeric heterochromatin and is thought to regulate gene expression. In mice, Atrx inactivation results in embryonic lethality whereas conditional forebrain specific Atrx ablation showed impaired development and disorganization of the cortex. Furthermore, ATRX phosphorylation was shown to be cell cycle dependant, suggesting an important role for ATRX in cell cycle regulation. In this study we investigated the effects of ATRX downregulation in cell culture models, using siRNA transient transfection, a clone expressing an shRNA targeted to ATRX, and Atrxnull MEFs. ATRX downregulated cells showed reduced growth rates and cell cycle defects at the G1 and S phases of the cell cycle. Moreover, ATRX ablation was associated with an altered Rb phosphorylation status and decreased expression of the cyclin A and E2F-1 proteins. Taken together our results suggest that ATRX may play a significant role in cell cycle progression that is pertinent for proper development.
Keywords: Biology, Molecular.; Biology, Cell.; Chemistry, Biochemistry.